Issues on women and problems in workplace from Islamic point of view - Ramli, Angraini; Elatrash, Radwan Jamal Yousef (IAIN Langsa, 2018)
The globalization and economic growth develop bigger chance especially to women to take a part in playing their role. Women education and strength are well established nowadays which can be potentially empowered in many public sectors. These phenomenahave caused positive and negative impacts to their live economically and socially. Islam provides the solutionsfor those social problems which effected by women involvement in public. This research describes several problemsappearingbecause of women taking their part in public sectors and how Islam provides the regulations and rules to protect the women’s fitrah and meet women development needs today.